2018
DOI: 10.1590/1678-5150-pvb-5503
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and biochemical indicators of maturity in foals and their relation to the placental features

Abstract: Newborn’s health is directly related to gestational conditions and placental efficiency. The aims of this study were: (1) To evaluate hematological and biochemical parameters of foals born from mares with placentitis at birth and at 24h of age, (2) to verify if placental pathology had any influence on neonatal maturity degree through hematological and biochemical response of those foals. According to placental findings (control and placentitis) and neonatal maturity degree (mature and immature), foals were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…A study evaluating RDW in human neonates has demonstrated that these values are negatively correlated to gestational length in all infants and remarkably higher in intrauterine‐restricted growth and premature neonates when compared to healthy full‐term newborns 21 . Higher MCV values have also been correlated to immaturity in neonatal foals born from mares with placentitis 33 . Here, we found that RDW had a negative correlation to gestational age, suggesting a link to foal maturity.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…A study evaluating RDW in human neonates has demonstrated that these values are negatively correlated to gestational length in all infants and remarkably higher in intrauterine‐restricted growth and premature neonates when compared to healthy full‐term newborns 21 . Higher MCV values have also been correlated to immaturity in neonatal foals born from mares with placentitis 33 . Here, we found that RDW had a negative correlation to gestational age, suggesting a link to foal maturity.…”
Section: Discussionsupporting
confidence: 56%
“…21 Higher MCV values have also been correlated to immaturity in neonatal foals born from mares with placentitis. 33 Here, we found that RDW had a negative correlation to gestational age, suggesting a link to foal maturity. We presume that a stronger correlation might be observed when evaluating the hematology in a larger number of animals, including premature foals.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations